Principles of Strategic Management Accounting - Masschelein, Stijn (Open textbook library., 2024)
This textbook explains the economic and sociological principles that underpin the use of strategic management accounting practices in organisations. Each chapter of the first part starts with a gentle, conversational introduction to the insights of one strand of academic literature and applies the insights to modern performance measurement and evaluation practices. The following parts apply the principles to specific accounting tools such as the budget, cost accounting, and the balanced scorecard. The textbook can be used in an advanced management accounting undergraduate unit or a post-graduate unit to give students a firm grounding to analyse measurement and evaluation practices in modern organisations. The textbook is meant to be a jumping off point for students and prepare them to analyse case studies and technical articles on strategic management accounting.